Downward migration of radiocaesium in organic soils across a transect in Scotland - Shand, C.A.; Rosén, K.; Thored, K.; Wendler, R.; Hillier, S. (Journal of environmental radioactivity, 2013)
Following the accident at the Chernobyl nuclear power plant in 1986, radioactive materials including 137Cs were distributed over large parts of the former Soviet Union and Europe. Due to the relatively long physical half-life of 137Cs (30.1 y) measurable activity concentrations can still be observed in the natural environment. We have determined the depth distribution of 137Cs from the testing of nuclear weapons in the atmosphere and Chernobyl, in eight highly-organic soils along an approximately east to west transect across the Central Highlands of Scotland. The 137Cs activity concentrations in the soil profiles, corrected for radioactive decay to May 1986, were between 2.8 and 14.4 kBq m−2. There were differences in the pattern of distribution of 137Cs in the soil profiles. The mean migration depth of 137Cs in the soil profiles was 12.2 cm with a range between 8.2 and 17.4 cm. Quantitative mineralogical analysis of the ash obtained after heating the soil to 400 °C indicated that clay minerals alone did not have a prime role in controlling the migration of 137Cs down the profile. ► In 1986 the Chernobyl accident contaminated soils across Europe with 137Cs. ► In 2008/2010 we measured 137Cs in 8 peaty soils from a transect across Scotland. ► The 137Cs activities were between 2.8 and 14.4 kBq m−2, decay corrected to 1986. ► The mean migration depths of 137Cs were between 8.2 and 17.4 cm. ► Clay minerals alone in the soils did not control the downward migration of 137Cs.